2018
DOI: 10.1002/uog.18989
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adenomyosis on pregnancy and perinatal outcomes in women with endometriosis

Abstract: The presence of diffuse adenomyosis in pregnant women with endometriosis is strongly associated with delivery of a SGA infant. Women with diffuse adenomyosis should be treated as being at high risk of placental dysfunction, and these pregnancies might therefore need closer monitoring. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 36 publications
(67 reference statements)
2
35
0
1
Order By: Relevance
“…Newly released research has found that women with endometriosis have an inclined tendency to have pregnancy complications, which include miscarriage as well as ectopic pregnancy. 4 Furthermore, according to the literature, women, who suffer from endometriosis would face with a higher tendency of preterm birth, [5][6][7][8] even though conflicting results exist. 9,10 IVF is considered as a common method in dealing with maternal endometriosis-related infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Newly released research has found that women with endometriosis have an inclined tendency to have pregnancy complications, which include miscarriage as well as ectopic pregnancy. 4 Furthermore, according to the literature, women, who suffer from endometriosis would face with a higher tendency of preterm birth, [5][6][7][8] even though conflicting results exist. 9,10 IVF is considered as a common method in dealing with maternal endometriosis-related infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our academic group demonstrated that the presence of diffuse adenomyosis in pregnant women affected by endometriosis is strongly associated with SGA infants, thus suggesting a causative relationship between diffuse adenomyosis and placental dysfunction [18].…”
Section: Discussionmentioning
confidence: 99%
“…Our academic group recently demonstrated that the presence of diffuse adenomyosis in women with endometriosis was more strongly associated with impaired placentation and delivery of SGA infants in comparison to patients with only endometriosis and with focal adenomyosis and concomitant endometriosis [18]; notably, these data may suggest a potential major role of adenomyosis in enhancing the risk of having these obstetrics adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The atypical presentation of endometrial tissue induces oxidative stress, chronic inflammation, uterine abnormal peristaltic motility, and disturbed sperm transport 1,2 . Therefore, abnormal implantation, decidualization, and placentation in adenomyosis have a negative impact on fetal well-being and further consequences, according to Barker hypothesis 3,4 .…”
Section: Introductionmentioning
confidence: 99%